ANALYSIS OF STUDENTS’ AND TEACHERS’ RESPONSE OF THE IMPLEMENTATION OF SCIENTIFIC APPROACH WITH PODCAST APP IN TEACHING LISTENING - Desyari Lestari Kurnanika; Cynantia Rachmijati (IKIP Siliwangi, 2021)
This research is aimed to analyze teachers and students respond in teaching listening skills to the Tenth Grade Students using a scientific approach with learning English podcast applications. This research uses qualitative descriptive, this research is purposed to collect the data both qualitative and quantitative approaches. questionnaires and Interviews. it was done in tenth-grade consist of 21 students in senior high school. The result shows that from two indicators are attention and relevance, from these indicators show that, most of the students respond stated agree in the indicators attention with percentage 471.4% with the number of frequencies 99 and for indicators relevance, most students stated neutral with percentage 228.6% with total frequency 48. Also, teacher responses show that students are quite enthusiastic and it is quite an effective way to teach listening. From this research, it can conclude most of the students choose to agree, that the use of podcast make students have a high motivation to the learn, improve retention, easy to understand the material, avoid the wrong concept, it is not boring, and improve listening comprehension, additionally teacher agree that podcast can make students quite enthusiastic during the learning activity. must include an abstract of 200 words or fewer. Keywords: Listening skill, podcast, respond, Motivation